Representações sociais em disputa: o movimento pela humanização do parto e do nascimento em São Carlos - Rocha, Carolina Neves da (2015)
Childbirth is not only a physical and biological event, but also a social and cultural one, which traditionally involved the whole community. With the institutionalization and appropriation of childbirth by Medicine, it has also appropriated women’s bodies, subjecting them to protocols and disregarding their individual, emotional and cultural aspects. In opposition to this model, which became hegemonic throughout the post-industrial western world, emerged movements of health professionals and women who claimed the humanization of delivery. In Brazil, this movement began in the 1980s and, along with international agencies such as WHO, influenced proposals of the Ministry of Health in the following decades. Since 2000’s, there was intense scientific literature on the subject, becoming an important interdisciplinary field. This study aimed to understand the social representations of the agents involved in the movement for humanization of childbirth in the city of São Carlos, where there was a significant amount of experiences and progress in the same direction proposed by the humanization. To achieve this goal, information from the literature on the subject, documentary analysis of public policies, semi-structured interviews and participant observations between the years 2013 and 2014 were triangulated. Social representations were analyzed by a theoretical framework formed from Theory of Social Representations and concepts from the literature, with the backdrop of public policies and the movement’s history. As a result, seized up a group consensus regarding the concept of humanization, which is the articulation of respecting women and their right to informed choice with a new practice in obstetrics, based on scientific evidence. Also agreed were the main Movement pillars identified, namely access to and dissemination of information based on evidence and the fight against obstetric violence. Finally, important disagreements have been found, such as the question if the universality was a goal of the Movement. Also, some contradictions and struggles were revealed by the discourses accessed, mainly related to internal and external relations established by the Movement. It was perceived as key findings the lack of articulation of this movement and its de-politicisation, factors that limited their activities towards changing the current obstetric model.